Право дитини на освіту: забезпечення реалізації можливостей та автономності - Селюков, В. С.; Seliukov, V. S.; ORCID: http://orcid.org/0000-0002-6690-6484 (Право і безпека. - 2015. - № 2 (57). - С. 38-45., 2015)
Розглянуто рівень автономності дітей при забезпеченні реалізації ними конституційного права на освіту. Особливу увагу приділено відмінностям, що характерні для різних вікових груп, залежно від виду освіти.

The international community and each country pay a great attention to legal regulation of human rights and freedoms. A special place in this area is given to the rights of the most vulnerable segments of society, one of which is children. The significance of children rights has its features, as children because of their age, psychological and physiological condition and lack of socialization can not completely independently (autonomously) realize their positive rights. One of the most essential children rights is the right on education, which is regulated by a large number of international and several national regulations. The national legislation for the regulation of the autonomy of a child in realizing the right on education is analyzed in the article. Such an analysis was possible because of a division of the complex right on education into element rights. They include the right on: parental education, pre-school education, school education, extraschool education, vocational education, higher education and self-education. Following such a list of children rights, the author provides data concerning the opportunities of children to make legally significant decisions to realize their right on education depending on the age and type of education. The problem of interpretation of parental education is highlighted, in the context of which it is emphasized on its isolation from the pre-school education. It is established that mostly children autonomy in realizing their right on education depends on their age. Legislation of Ukraine directly or indirectly sets the age limits concerning different types of education, but there are some exceptions. The right on parental education is barely regulated, therefore it is emphasized on the fact that it can be realized even after reaching the lawful age; self-education does not depend on the legal regulation of this process. It is concluded that it is understatement of children autonomy (under implementation of certain rights on education) and inadequate legal regulation reduce a real opportunity of a child to use fully his/her constitutional rights.

Рассмотрен уровень автономности детей при обеспечении реализации ими конституционного права на образование. Особое внимание уделено различиям, характерным для разных возрастных групп, в зависимости от вида образования.
Seliukov, V.S. (2015), “Children right on education: guaranteeing implementation of possibilities and autonomy” [“Pravo dytyny na osvitu: zabezpechennia realizatsii mozhlyvostei ta avtonomnosti”], Pravo i Bezpeka, No. 2, pp. 38–45.
Селюков, В. С. Право дитини на освіту: забезпечення реалізації можливостей та автономності // Право і безпека. - 2015. - № 2 (57). - С. 38-45.
Keywords: Конституційне право. Constitutional Law. Конституционное право; Міжнародне право .International Law. Международное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; дитина; право на освіту; автономність дитини; механізм реалізації права на освіту; забезпечення права на освіту; child; right on education; autonomy of a child; mechanism of realizing the right on education; guaranteeing the right on education; ребёнок; право на образование; автономность ребёнка; механизм реализации права на образование; обеспечение права на образование